What Do We Say about Ourselves and What Does It Mean? Yet Another Look at Economics Department Research - Thursby, Jerry G (Journal of Economic Literature, 2000)
Statistical and programming techniques are used to examine economics department quality rankings and how resources and research output are related. Four questions are asked using the National Research Council's 1993 survey. Are there significant differences in department quality scores? How are quality scores related to publications, citations and numbers of Ph.D.s produced? What is the relation between research output and department resources? How well do departments generate research in comparison with other departments with similar levels of resources? What I find is that resources determine outputs, outputs determine opinions (which are generally diffuse) and most departments efficiently use their resources.